Thermal Mitigation Behaviors of Captive Blue Peafowls and Visitors’ Outdoor Thermal Comfort: A Case Study at Jinan Zoo, China - Zhiqiang Zhou; Ran Jiao; Huijian Hu; Tauheed Ullah Khan (Animals)
Zoos play dual roles in wildlife conservation and in providing recreational experiences for visitors in urban green spaces. However, the impacts of thermal environments on both visitor comfort and captive animal welfare remain unexplored, which is an important aspect to address for improving overall zoo management. This study investigated thermal conditions at Jinan Zoo, China, over 20 summer days. Questionnaires were used to collect visitor thermal comfort and viewing satisfaction, while the thermal mitigation behaviors of 70 blue peafowls were recorded under various thermal conditions on-site. The findings showed that the wet-bulb globe temperature (WBGT) neutral range for visitors was 20.1–24.4 °C, with a significant drop in visitor numbers when WBGT exceeded 35.5 °C. Visitors with higher animal viewing satisfaction (aVSV) scores were more heat tolerant. The blue peafowls reduced their activity levels and displayed feather-spreading and gular flutter at WBGT levels of 26.4–30.4 °C, especially during peak visitor hours. Our study also showed that visitor thermal sensation was most affected by radiation, whereas blue peafowl heat stress was likely influenced by air temperature, followed by humidity and radiation. These findings offer practical insights for designing zoo enclosures and visitor areas to improve comfort and animal welfare in hot weather.